Dietary supplementation with compound microecological preparations: effects on the production performance and gut microbiota of lactating female rabbits and their litters - Chengcheng Zhao; Youhao Li; Hui Wang; Ahamba Ifeanyi Solomon; Shuhui Wang; Xianggui Dong; Bing Song; Zhanjun Ren (Microbiology Spectrum)
ABSTRACT Early weaning is frequently accompanied by a significant increase in diarrhea and mortality rates, which reduces rabbits’ performance. Although antibiotics can reduce pathogenic bacteria, they also harm beneficial microorganisms and disrupt the normal intestinal microbiota balance. In order to find non-residue and non-toxic alternatives to antibiotics to ensure the safety of animal products, we conducted a study on the effect of compound microecological preparations supplementation on lactating female rabbits and their offspring. A total of 60 female rabbits were randomly assigned to four groups: CON, supplemented with probiotics at 3, 6, and 9 g/female rabbit/day from day 24 of gestation until weaning. We observed that probiotics supplementation significantly enhanced production performance (P < 0.05), immune and antioxidant function (P < 0.05), as well as intestinal flora composition in lactating rabbits and their offspring. Notably, compared with the control group, the experimental group exhibited a 19.23%, 44.22%, and 24.57% increase in milk yield (P = 0.002). Regarding rabbit growth performance, the average body weight of young rabbits in the experimental group showed a significant increase of 3.59%, 10.22%, and 6.74% at day 35 (P = 0.022), whereas the average daily gain (ADG) of rabbits aged between 21 and 35 days was significantly elevated by 4.94%, 17.06%, and 6.28% in the experimental group (P < 0.001). In conclusion, probiotics supplementation can significantly enhance lactation performance, promote growth and disease resistance in rabbits, as well as improve intestinal health when administered at a dosage of 6 g/day. Moreover, the limited sample size in this study may hinder the detection of subtle effects, and augmenting the sample size will bolster the reliability of the study findings.IMPORTANCEThe intestinal environment of rabbits is fragile and susceptible to environmental influences, leading to inflammatory intestinal diseases. Adding antibiotics to rabbit feed can achieve the effect of preventing and treating inflammation, which can also lead to the imbalance of the gut microbiota and residual antibiotics in agricultural products. Composite probiotics are live microbial feed additives composed of various ratios of probiotics and have become the most promising alternative to antibiotics due to their residue-free and non-toxic properties. The aim of this study was to investigate the impact of compound probiotics on lactating female rabbits and their offspring. Our findings highlight the potential of compound microecological preparations as an effective strategy for enhancing lactation performance, immune function, and antioxidant capacity in rabbits. The supplementation of probiotics through rabbit milk offers a promising approach to optimize the growth and health outcomes of newborn rabbits.